The Experiences of Women Possessing a Genetic Predisposition to Developing Breast Cancer: Learning to Live With Uncertainty - DiMillo, Julia (University of Ottawa (Canada), 2010)
Genetic testing to determine whether a woman carries a BRCA1 or BRCA2 mutation, which may entail an up to 80% lifetime risk of developing breast cancer, is relatively recent. As there is an apparent void in the literature investigating the experiences of these women, and few qualitative studies of this nature exist, six women identified as carriers were invited to participate in semi-structured interviews. The grounded theory method was utilized and through findings emerged two core categories: Context Following the Receipt of the Test Results and Living with the BRCA Genetic Mutation: An Uncertain Conclusion to an Unending Process. Specifically, following the receipt of their test result, participants reported changes in their self-perception and perception of others. Over time, participants described living with the BRCA gene mutation and its medical consequences. Particularly significant findings consisted of participants feeling less like a woman, feeling stigmatized, and living with unending uncertainty.
Keywords: Women's Studies.; Psychology, Counseling.